2014
DOI: 10.1053/j.gastro.2014.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies Variants Associated With Autoimmune Hepatitis Type 1

Abstract: In a genome-wide association study, we associated AIH type 1 with variants in the major histocompatibility complex region, and identified variants of SH2B3and CARD10 as likely risk factors. These findings support a complex genetic basis for AIH pathogenesis and indicate that part of the genetic susceptibility overlaps with that for other immune-mediated liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
223
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(231 citation statements)
references
References 58 publications
5
223
1
2
Order By: Relevance
“…They tended to have earlier disease onset and lower frequency of concurrent immune diseases [39] . Beyond HLA-related genes, a recent genome-wide association study in AIH verified the association of AIH-1 with variants in the MHC region, but also identified SH2B3 as the first non-HLA genetic factor for AIH and indicated that AIH-1 shares part of the genetic susceptibility with other immune-mediated diseases [40] . Its relevance to the prevalence of concurrent AIDs is as yet uncertain.…”
Section: Effects Of Aih Types Age Gender and Genetic Backgroundmentioning
confidence: 93%
“…They tended to have earlier disease onset and lower frequency of concurrent immune diseases [39] . Beyond HLA-related genes, a recent genome-wide association study in AIH verified the association of AIH-1 with variants in the MHC region, but also identified SH2B3 as the first non-HLA genetic factor for AIH and indicated that AIH-1 shares part of the genetic susceptibility with other immune-mediated diseases [40] . Its relevance to the prevalence of concurrent AIDs is as yet uncertain.…”
Section: Effects Of Aih Types Age Gender and Genetic Backgroundmentioning
confidence: 93%
“…Hence the conflictory evidence of inflammation not resulting in fibrosis in pediatric LT versus other inflammatory hepatic diseases. In AIH, the HLA-DRB1*03/04 allele is considered an independent predictor of portal fibrosis (Montano-Loza et al, 2006;de Boer et al, 2014;Liberal et al, 2015). As AIH is the prototype of immune dysregulation-mediated hepatic disease, examining its role in LT recipients is the next logical step: we sought to evaluate "idiopathic" allograft changes by analysing serial PBs in a complication-free LT recipient cohort.…”
Section: Introductionmentioning
confidence: 99%
“…These associations have been recently confirmed in the first AIH genome-wide association study [27] . In paediatrics, AIH-1 is associated with the possession of HLA-DRB1 * 03 [3] , while susceptibility to AIH-2 is associated with HLA-DR * 03 and HLA-DR * 07 [28,29] .…”
Section: Geneticsmentioning
confidence: 61%